Methods of Teaching Stylistics at Secondary Education - S. A. Glazirina (International Journal on Human-Computing Studies, 2022)
Nowadays modern methods of teaching stylistics may be a generalization of the educating encounter inside the system of the conventional fashion created by V.V. Vinogradov, and approaches, which include cognitive stylistics. This article substantiates to present stylistics into the school educational programs of the Uzbekistan. Dialect of the components of cognitive stylistics permits students to learn, to practice and to distinguish the association between the elaborating the nature of dialect and the most cognitive forms, uncovers elaborative meaning and their part in discourse communication.